Pengaruh Dana Desa Dan Alokasi Dana Desa Terhadap Tingkat Kemiskinan Di Kecamatan Wera (Studi Pada Desa Di Kecamatan Wera Kabupaten Bima Tahun 2017-2019) - Yuspriyono Yuspriyono; Jeni Susyanti; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis research was conducted to examine the effect of village funds and allocation of village funds on poverty levels in Wera Sub district. The population used in this study was 14 villages in Wera Sub district, Bima Regency for the 2017-2019 periode. The sampling method is purposive sampling in accordance with predetermined criteria. The number of samples was 45 people, consisting of 14 village heads, 14 village secretaries, 14 village treasurers, 1 sub-district head, 1 sub-district secretary and 1 head of Wera sub-district social service. The data in this study use multiple linear regression, classic assumptions and hypothesis testing.The results of this study indicate that partially village funds have no significant effect on poverty levels, and the allocation of funds has a significant effect on poverty levels. While simultaneous village funds and village fund allocations significantly influence poverty levels. Keywords: Village Funds, Village Fund Allocation, Poverty, Wera Subdistrict